Modifikasi Hanbok dengan Kain Songket Motif Nampan Perak - Wijaya, Rekha Nurani; Astuti, Astuti Astuti (Institut Seni Indonesia Yogyakarta, 2024)
AbstractHanbok (한복) Hanbok is a traditional Korean clothing consisting of Jeogori (jacket) and Chima (skirt) / Baji (pants). Generally, Hanbok is only used on big celebration days or festivals. However, Hanbok is still used as daily clothing for Korean people who still live in traditional villages such as Chunghak-dong on Mount Jiri. Hanbok is made of hemp fabric which is neatly woven and of high quality. The characteristics of the cloth used to make Hanbok have similarities with songket cloth. Songket is a traditional handwoven fabric. In general, songket is woven with gold and silver threads. The songket motif used is a nampan perak motif. The nampan perak motif depicts the glory and obedient attitude of the princes and priyayi to their leader (Sultan). Therefore, the purpose of making this dress is to produce a fashion product that is rich in cultural values. The method used is the method of observation, literature study, as well as observation and problem solving.AbstrakHanbok (한복) Hanbok merupakan pakaian tradisional masyarakat Korea yang terdiri dari Jeogori (jaket) dan Chima (rok) / Baji (celana). Umumnya Hanbok hanya digunakan pada hari perayaan besar atau festival saja. Namun, Hanbok masih digunakan sebagai pakaian sehari hari masyarakat Korea yang masih tinggal di desa-desa tradisional seperti Chunghak-dong di gunung Jiri. Hanbok dibuat dengan kain rami yang ditenun rapi serta memiliki kualitas yang tinggi. Karakteristik kain yang digunakan untuk membuat Hanbok memiliki kesamaan dengan kain songket. Kain songket merupakan kain tenun tradisional yang ditenun dengan tangan. Pada umumnya kain songket ditenun dengan benang berwarna emas dan perak. Motif kain songket yang digunakan adalah motif nampan perak. Motif nampan perak menggambarkan kejayaan dan sikap patuh para pangeran dan priyayi kepada pimpinannya (Sultan). Maka dari itu, tujuan pembuatan busana ini adalah menghasilkan satu produk busana yang kaya akan nilai budaya. Metode yang digunakan adalah metode observasi, studi literature, serta pengamatan dan pemecahan masalah.